1995
DOI: 10.1002/0471140864.ps0605s00
|View full text |Cite
|
Sign up to set email alerts
|

Folding and Purification of Insoluble (Inclusion Body) Proteins from Escherichia coli

Abstract: Heterologous expression of recombinant proteins in E. coli often results in the formation of insoluble and inactive protein aggregates, commonly referred to as inclusion bodies. To obtain the native (i.e., correctly folded) and hence active form of the protein from such aggregates, four steps are usually followed: (1) the cells are lysed and the are aggregates, (2) the cell wall and outer membrane components of the aggregates are removed, (3) the aggregates are solubilized (or extracted) with strong protein de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…BLI can be used to determine whether a protein is present in a sample by means of specific antibodies. Purification of vimentin and vimentin fragments has been described elsewhere (Strelkov et al, 2001); expression and purification strategies can also be found elsewhere (Palmer & Wingfield, 2012; Wingfield, Palmer, & Liang, 2014). Purification of proteins tagged with His 6 or GST is much simpler than purification of untagged proteins (Palmer & Wingfield, 2012; Wingfield et al, 2014).…”
Section: Investigating Vimentin–protein Interactionsmentioning
confidence: 99%
“…BLI can be used to determine whether a protein is present in a sample by means of specific antibodies. Purification of vimentin and vimentin fragments has been described elsewhere (Strelkov et al, 2001); expression and purification strategies can also be found elsewhere (Palmer & Wingfield, 2012; Wingfield, Palmer, & Liang, 2014). Purification of proteins tagged with His 6 or GST is much simpler than purification of untagged proteins (Palmer & Wingfield, 2012; Wingfield et al, 2014).…”
Section: Investigating Vimentin–protein Interactionsmentioning
confidence: 99%
“…Using PCR with appropriate primers, an 83-residue segment from the N terminus of Pik1 consisting of residues , was tagged at its C terminus with an His 6 tract, inserted as an NcoI-XhoI fragment into the corresponding sites in the vector, pET23d, and expressed in E. coli strain BL21(DE3), as described above; in this construct, the Pik1-derived sequence is preceded by a 2-residue leader (Met-Ala-). Pik1-(110 -192)-(His) 6 was produced primarily in inclusion bodies, which were solubilized using 6 M guanidine hydrochloride (49) All NMR experiments were performed at 37°C on a Model DRX-500 or DRX-600 NMR spectrometer (Bruker Instruments, Billerica, MA) equipped with a four-channel interface and a triple-resonance probe with triple-axis pulsed field gradients as described before (35). The NMR spectra were processed and analyzed as described previously (50).…”
Section: S]met and [mentioning
confidence: 99%
“…) was MutS. However, a vast majority (ϳ80%) of the recombinant protein precipitated as inclusion bodies (30). This was corrected by reducing the isopropyl-1-thio-␤-D-galactopyranoside to 0.05-0.1 mM and lowering the growth temperature to 25°C.…”
Section: Purification Of Hexameric Histidine Recombinant Muts-mentioning
confidence: 99%